Practical Issues for Atom Probe Tomography Analysis of III-Nitride Semiconductor Materials. (30th April 2015) - Tang, Fengzai; Moody, Michael P.; Martin, Tomas L.; Bagot, Paul A.J.; Kappers, Menno J.; Oliver, Rachel A.
Abstract: Various practical issues affecting atom probe tomography (APT) analysis of III-nitride semiconductors have been studied as part of an investigation using a c -plane InAlN/GaN heterostructure. Specimen preparation was undertaken using a focused ion beam microscope with a mono-isotopic Ga source. This enabled the unambiguous observation of implantation damage induced by sample preparation. In the reconstructed InAlN layer Ga implantation was demonstrated for the standard "clean-up" voltage (5 kV), but this was significantly reduced by using a lower voltage (e.g., 1 kV). The characteristics of APT data from the desorption maps to the mass spectra and measured chemical compositions were examined within the GaN buffer layer underlying the InAlN layer in both pulsed laser and pulsed voltage modes. The measured Ga content increased monotonically with increasing laser pulse energy and voltage pulse fraction within the examined ranges. The best results were obtained at very low laser energy, with the Ga content close to the expected stoichiometric value for GaN and the associated desorption map showing a clear crystallographic pole structure.